Strategi Kepala Madrasah dalam Meningkatkan Budaya Literasi di Madrasah Tsanawiyah - Bajuri Bajuri; Barnoto (Program S3 Pendidikan Islam Institut Pesantren KH. Abdul Chalim Pacet Mojokerto, 2022)
The purpose of this study was to determine the role of the madrasah head in increasing literacy culture at MTs Sunan Ampel KumpuIrejo Parengan Tuban, to find out the supporting and inhibiting factors in increasing the iteration culture at MTs Sunan Ampel KumpuIrejo Parengan Tuban, to find out the strategy for increasing literacy culture in increasing interest in reading at MTs Sunan Ampel Kumpulrejo Parengan Tuban. This study uses a qualitative approach in which this approach produces descriptive data in the form of written or spoken words from people and observable behavior. The results of this study indicate that: 1) The role of the madrasa head is as an educator, manager, administrator, supervisor, leader, innovator, and motivator. 2) There are several supporting and inhibiting factors in developing a literacy culture. Supporting factors include The active role of madrasa residents, Support from parents of students. In addition, there are several inhibiting factors, namely: limited collection, and the influence of technology. 3) In developing a literacy culture, the head of MTs Sunan Ampel has several strategies used including Developing a library, Providing fiction, non-fiction, and reference books. Development of reading areas, 15-minute reading program, Development of literacy-themed madrasah activity programs.